GROWTH AND YIELD OF CHILLI ( GROWTH AND YIELD OF CHILLI (CAPSICUM ANNUUM L.) AS INFLUENCED BY DIFFERENT GROWTH REGULATORS - RAJ, A. CHANDINI; K, HOLEBASAPPA; HORE, J. K. (The Bioscan, 2015)
The experiment was carried out at Horticultural Research Station, Mondouri, Bidhan Chandra Krishi Viswa vidyalaya during 2012-14 in chilli cv. Beldanga. Three concentration of four growth regulators namely NAA (25, 50 and 75 ppm), GA3 (20, 40 and 60 ppm), 2, 4-D (5, 7.5 and 10 ppm) and ethrel (300, 400 and 500 ppm) were included in this investigation. The regulators were applied as foliar spray at 30 and 60 days after transplanting. There were altogether 13 treatments including control (water spray).In both the years, the seedlings were transplanted during middle of November in 2m x 1.6m plot at 50x40 cm spacing accommodating 16 plants per plot. The experiment was laid out in RBD with three replication. The NPK dose was 150: 80: 80 kg/ha.Among different treatments maximum plant spread (E-W) [46.97 cm], number of fruits per plant (94.83), fruit length (6.80 cm), yield per plot (2.72kg/3.2m2) and projected yield per hectare (6.37 t) were observed in plants raised from application of NAA 75 ppm.Maximum plant height (75.60 cm), plant spread in North-South direction (46.53 cm), number of days to flowering (47.56) and maximum fruit diameter (1.24 cm) were recorded in GA3 60 ppm treated plants. The projected yield under untreated control was 4.34 t/ha.From yield maximization point of view the most effective treatment was NAA 75 ppm under alluvial plains of West Bengal for production of chilli